Hubungan Pengetahuan Ibu Tentang Stimulasi Perkembangan Anak Dengan Keterampilan Ibu Dalam Melakukan Stimulasi Perkembangan Anak - Neny Yuli Susanti; Robiatul Adawiyah (Universitas STRADA Indonesia, 2020)
Knowledge about children and have skills of stimulating needs of children at each stage of development, so that children's intelligence can develop with maximum age. Age 0-2 years is a very important time considering the brain development occurs very rapidly at the age under 2 years, this is called a critical period of development, and is a good time to make a recovery, if there is a developmental disorder. Technique of collecting knowledge data using questionnaire sheet and skill data using Checklist executed at May 2018. Data analysis using statistical test with SPSS software that is